Articulated Intramedullary Pin-Hybridized Circular External Skeletal Fixator Construct for Stabilization of Comminuted Femur Fractures in Three Cats - Blatt, Braiden M.; Scheuermann, Logan M.; Lewis, Daniel D. (VCOT Open, 2025)
This case series describes the clinical results following stabilization of comminuted diaphyseal femoral fractures, two of which extended into the proximal metaphyseal region, using an articulated intramedullary (IM) pin-hybridized circular external fixator construct in three cats. An IM pin was placed to initially align and stabilize each fracture via an open reduction. The fixator construct consisted of a proximal partial ring arch and a distal stretch ring. Half-pins were used as fixation elements on the proximal ring, whereas olive wires were used as fixation elements on the distal ring. All three fractures were acceptably reduced and aligned. The constructs afforded functional use of the limb during the post-operative convalescent period with few complications. The constructs were maintained for 8, 15, and 16 weeks until there was sufficient radiographic fracture healing for fixator removal. In one cat, the IM pin was maintained following fixator removal and was articulated with a single retained half-pin engaging the greater trochanter and femoral neck. All three cats were reported to have acceptable pelvic limb function at 12, 25, and 93 months following surgery, with two of the cats reported to have occasional, intermittent nominal lameness.
Keywords: circular external skeletal fixator; cats; comminuted diaphyseal femur fracture; hybridized